Researching and Development of an Autonomous Underwater Vehicles with Capability of Collecting Solar Energy - Nguyen, Van Tuan; Dinh, Van Phong; Nguyen, Chi Hung (Smart Systems and Devices, 2021)
Autonomous Underwater Vehicles (AUV) is an unmanned underwater device with capability of performing a variety of missions in the water environment such as ocean operation, offshore waters, polluted water investigation including: marine scientific research, maritime monitoring, exploration, marine economics, oil and gas, security and defense, surveillance and measurement and in rescue and salve. In this article, the authors developed a model of AUV with retractable wings and evaluate the efficiency of solar energy collection. The establishment of the controller to adapt the stability requirements, in accordance with the model of equipment S-AUV (Solar - Autonomous Underwater Vehicles) was built. The hydrodynamic equations with the predefined conditions were modeled and solved. The Hierarchical Sliding Mode Controller (HSMC) for the S-AUV were applied in this research. Experimental results showed that the efficiency of the collection of the solar cell has been significantly improved comparing to a diving equipment without retractable energy wings. In addition, the simulation results showed that the developed controller performed much better control quality, adhering to the set value with the error within the permissible limit.